27-Hydroxycholesterol Promotes the Transfer of Astrocyte-Derived Cholesterol to Neurons in Co-cultured SH-SY5Y Cells and C6 Cells - Wang, Yushan; Zhang, Xiaona; Wang, Tao; Liu, Wen; Wang, Lijing; Hao, Ling; Ju, Mengwei; Xiao, Rong (Frontiers in Cell and Developmental Biology, 2020)
Abnormality in cholesterol homeostasis in the brain is a feature of Alzheimer’s disease (AD). 27-Hydroxycholesterol (27-OHC) has been identified as a possible biomarker of AD, but its effects on cholesterol metabolism have not been fully characterized. This study was aimed to investigate the impacts of 27-OHC on cholesterol metabolism in nerve cells. SH-SY5Y cells and C6 cells were co-cultured and treated with 5, 10 and 20μM 27-OHC for 24 h. Results showed 27-OHC decreased cholesterol levels and up-regulated the expression of transport-related proteins in C6 cells. In SH-SY5Y cells, 27-OHC increased cholesterol accumulation, especially on plasma membrane (PM), which was consistent with the up-regulation of expressions of cholesterol endocytosis receptors, lipid raft related proteins and cholesterol esterase. Simultaneously, accumulation of membrane cholesterol promoted cholesterol conversion to 24S-OHC by CYP46A1(24S-hydroxylase) transfer from the endoplasmic reticulum (ER) to PM. Besides, Aβ levels were elevated in SH-SY5Y cells after 27-OHC treatment. Our results suggest that 27-OHC motivates the transfer of astrocyte-derived cholesterol to neurons. Although there exists a feedback mechanism that excessive cholesterol promotes its conversion to 24S-OHC, the increased cholesterol induced by 27-OHC couldn’t be wholly offset in neurons.